Long-term results of tonsillectomy in professional opera singers: a pilot study - Clarós, Pedro; Sobolewska, Aleksandra; Pujol, María del Carmen; Clarós-Pujol, Astrid; Clarós, Andrés (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The primary goal of this study was to evaluate the long-term influence of tonsillectomy on the quality of life and voice performance of opera singers. Survey study which was reviewing the long-term effects of tonsillectomy. Methods: Retrospective review of patients’ records and surveys in which patients have answered the questions about the influence of tonsillectomy on their voice. A total group of 30 singers was included in the study. They answered the questions about the indications for surgery, symptoms, and changes in their voice after surgery. The study group consisted of 19 women and 11 men. Mean age was 18.53 years old at the moment of surgery. The group included eleven sopranos, six mezzos, two contraltos, four tenors, five baritones, and one bass singer. Results: A most common indication for tonsillectomy in opera singers was recurrent tonsillitis and was present in over 83% of cases. After surgery, the voice performance was better in 60% of cases, breathing improved in 50% of cases, voice emission was higher in 53% of cases. Over 80% of singers would recommend that surgery to another opera singer. Conclusions: Singers evaluated long-term influence of tonsillectomy as positive. Over 80% admitted improved effect on emission and the function of voice.